High Blow-By Pressure Failure Quantification of Doosan Excavator DX300LCA Using Bayesian Network - Abdul Maajid Al Banna; Adhitya Ryan Ramadhani (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Various types of failure are likely to occur in heavy equipment operating in the mining sector, such as high blow-by pressure. The impact of this failure is a loss of engine power so that the unit cannot be used. This has the potential for work accidents to occur because the unit stops operating in a hazardous area. Therefore, the factors and dependencies that influence the occurrence of high blow by pressure will be discussed using the Fault Tree Analysis method and then the results will be used in the Bayesian Network method to do failure quantification. Meanwhile, the probability of high blow-by pressure occurring has a value of 0.0049 with the main cause being failure to compress the air with a sensitivity value of 80%. These results require companies to focus preventive maintenance activities on the engine combustion chamber to prevent similar things from happening. Beragam jenis kegagalan sangat mungkin terjadi pada alat berat yang beroperasi di sektor tambang, seperti high blow-by pressure. Dampak dari kegagalan ini ialah hilangnya tenaga mesin sehingga unit tidak dapat digunakan. Hal tersebut berpotensi untuk terjadinya kecelakaan kerja karena unit berhenti beroperasi di hazardous area. Maka dari itu, faktor-faktor yang mempengaruhi terjadinya high blow by pressure dan keterkaitannya akan dibahas menggunakan metode Fault Tree Analysis yang kemudian hasilnya akan digunakan pada metode Bayesian Network untuk dilakukan kuantifikasi kegagalan. Adapun, probabilitas terjadinya high blow-by preessure ini memiliki nilai sebesar 0,0049 dengan penyebab utama karena adanya kegagalan dalam mengompresi udara dengan nilai sensitivitas sebesar 80%. Hal tersebut mengharuskan perusahaan untuk memfokuskan kegiatan preventive maintenance pada ruang bakar mesin untuk mencegah hal serupa terjadi.